Uveal Melanoma in Asians: A Review - Manchegowda, Pradeep (Ocul Oncol Pathol, 2021)
Despite limited data, some differences in the clinical profile can be observed in Asian population when compared with presentation of uveal melanoma (UM) in white population. The incidence of UM is higher in Whites than in Asians. For the purpose of comparison with Asian population, data from North America, Europe, and Australia were considered as that of “white” population. The annual incidence of UM has been reported to be 5–6 cases/million in whites. The incidence in different parts of Asia is estimated at 0.2–0.6 per million. The age of presentation is around 40–55 years in Asians, which is younger when compared to that of whites (mean age of 58 years). At presentation, mean basal diameter of tumors in Asians is greater compared to whites but overall, medium-size tumors are most common. Clinical presentation is straightforward in majority of cases with retinal detachment, acute glaucoma, uveitis, cataract, or vitreous hemorrhage as common symptoms. Epithelioid cell-type variant carries the worst prognosis. Management options for choroidal melanoma include transpupillary thermotherapy, plaque radiotherapy, charged particle irradiation, local resection, enucleation, or orbital exenteration. Most commonly used modalities are enucleation and plaque radiotherapy.